Do reexcisions impair aesthetic outcome in breast conservation surgery?: exploratory analysis of a prospective cohort study - Heil, Jörg; Breitkreuz, Kathrin Anna; Golatta, Michael; Busch, Elena; Dahlkamp, Julia; Rom, Joachim; Schütz, Florian; Blumenstein, Maria; Rauch, Geraldine; Sohn, Christof (Annals of surgical oncology, 2012)
Purpose: Reexcision is a clinically relevant aspect of oncological breast conservation surgery. The influence of reexcision on aesthetic outcome is described differently in the literature. Our aim was to analyze this question in a well-defined cohort with standardized study instruments. Methods: A total of 439 patients from a prospectively followed cohort were included in this analysis. Aesthetic results were assessed by the Breast Cancer Treatment Outcome Scale (BCTOS) aesthetic status. Dates of assessments were shortly after surgical interventions and before surgery. Group comparison was performed between patients with reexcisions (80 cases; 18%) and patients without reexcision (359 cases; 82%). We considered variables of differing distribution between the two groups that could hypothetically influence BCTOS aesthetic status in a nonparametric analysis of covariance (ANCOVA). Results: The aesthetic status of patients with reexcisions was found to be significantly worse than for patients with a single breast conservation surgery (P < 0.0001) when tested by a nonparametric ANCOVA model. Because patients with reexcisions had more noninvasive tumors (25% vs. 8%, P = 0.0001) and tumors were larger in patients with reexcision (P = 0.01), we included these variables as possible covariates in the multivariate model. The model was adjusted for the BCTOS aesthetic status before and shortly after the first surgery. Conclusions: Our findings suggest that reexcision in breast conservation surgery impairs aesthetic outcome, at least when assessed shortly after surgery.